Investment Treaties and the Internal Vetting of Regulatory Proposals: A Case Study from Canada. (21st January 2016) - Van Harten, Gus; Scott, Dayna Nadine
Abstract: In this article, we report findings on whether trade and investment agreements that allow for investor–state dispute settlement (ISDS) contribute to regulatory chill. The study focused on whether ISDS contributed to changes in internal vetting of government decisions related to environmental protection in the province of Ontario, Canada. Our main source of information was confidential interviews with insiders, mostly current or former officials in ministries with an environmental or trade mandate. We aim to advance understanding of litigation risk and government decision-making with a focus on ISDS.